Effectiveness Of Interactive Methods In Teaching Several Methods Of Factoring Polynomials - Ravshanova Madina Ilhom qizi (Genius Journals, 2025)
This article analyzes the importance of using interactive methods in teaching the topic “Applying various methods of factoring polynomials” in mathematics lessons at general education schools. Recommendations are given on using interactive methods such as “State the rule correctly” and “Who is quick and skilled?” during the lesson to increase students’ active engagement, ensure thorough understanding of the topic, and promote independent thinking. The application of various methods for factoring polynomials based on practical examples is highlighted
Keywords: polynomial; interactive method; short multiplication formula